2020
DOI: 10.3390/polym12030665
|View full text |Cite
|
Sign up to set email alerts
|

PEEK Composites as Self-Lubricating Bush Materials for Articulating Revolute Pin Joints

Abstract: In this study, bearing bushes made of polyetheretherketone (PEEK), 30 wt % carbon fibre reinforced PEEK, 30 wt % glass fibre reinforced PEEK, each 10 wt % of PTFE, graphite and carbon fibre modified PEEK were investigated on a purpose built pin joint test rig. The unlubricated friction and wear behaviour was assessed in sliding contact with a 300M shaft, subjected to a nominal pressure of 93 MPa, articulating sliding speed of 45 °/s. The worn surface and the subsurface layer were studied using optical profilom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Because of the combination of excellent chemical resistance, thermal stability, and mechanical properties [ 1 , 2 , 3 ], polyetheretherketone (PEEK), a kind of semi-crystalline polymer, and its composites have attracted a great deal of interest from both scientists and engineers [ 4 ]. These kinds of polymers possess great potential to replace conventional metal materials because of their high strength-to-weight ratios, especially for the aviation and space industry [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the combination of excellent chemical resistance, thermal stability, and mechanical properties [ 1 , 2 , 3 ], polyetheretherketone (PEEK), a kind of semi-crystalline polymer, and its composites have attracted a great deal of interest from both scientists and engineers [ 4 ]. These kinds of polymers possess great potential to replace conventional metal materials because of their high strength-to-weight ratios, especially for the aviation and space industry [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suresha et al reported a self-lubricating nature of carbon fiber from the abrasion test [ 27 ]. Zhu et al conducted the pin joint test of graphite and carbon fiber modified polymer, and the self-lubricating carbonous characteristics were found by observing worn surfaces and wear debris [ 28 ]. In addition, these carbonous materials could create tribofilm.…”
Section: Tribological Test Of Nano-solid Lubricantsmentioning
confidence: 99%
“…Although the traditional biomedical titanium alloy has good tribological properties and compatibility in vivo circumstances, there were some obvious problems such as insufficient strength and rigidity, and the wear debris side effects in applications [1][2][3][4][5][6][7]. In the development of bone repair biomaterials, poly-ether-ether-ketone (PEEK) modified reinforced composites have been developed by leaps and bounds [5,6]. PEEK is a new type of semi-crystalline thermoplastic polymer, which has the advantages of elastic modulus closing to cortical bone, good biocompatibil-ity, constant physical and chemical properties and mechanical properties, and no artifacts in magnetic resonance imaging (MRI) scanning.…”
Section: Introductionmentioning
confidence: 99%